Linking maize yields in Veneto Italy, to large-scale atmospheric variability, circulation regimes and weather types. (5th December 2022) - Salinger, M. J.; Verdi, L.; Dalla Marta, A.; Dalu, G.; Baldi, M.; Messeri, G.; Vallorani, R.; Morabito, M.; Crisci, A.; Altobelli, F.; Orlandini, S.; Gozzini, B.; et al.
Abstract: This paper describes the relationships between large-scale modes of climate variability and its related weather types with the fluctuations in the yield of maize crops in Veneto, Italy. The teleconnections analysed in this work are the winter North Atlantic Oscillation (NAO) and the summer North Atlantic Oscillation (SNAO); the West African monsoon (WAM) and the Intertropical Front (ITF). Despite that these indices are not rigorously linked to one another, they result in being considerably related to atmospheric circulation regimes and associated weather types. They have an impact on temperature and precipitation patterns in Italy and on yields of maize crops in Veneto, a region located in northeast Italy. Yields are strongly affected by large-scale temperate and tropical variability directly through three main circulation regimes. Troughing weather regimes that produced below average temperatures depress yields over the entire Veneto region, as does the zonal regime that affects rainfall. Results confirm the relevance of large-scale modes and associated weather regimes and types on maize crop yields fluctuations in Veneto.